A CDT-Based Heuristic Zone Design Approach for Economic Census Investigators. (23rd November 2015) - Cheng, Changixu; Song, Xiaomei; Yang, Jing; Hu, Xiatian; Shen, Shi; Wang, Lijun
Abstract : This paper addresses a special zone design problem for economic census investigators that is motivated by a real-world application. This paper presented a heuristic multikernel growth approach via Constrained Delaunay Triangulation (CDT). This approach not only solved the barriers problem but also dealt with the polygon data in zoning procedure. In addition, it uses a new heuristic method to speed up the zoning process greatly on the premise of the required quality of zoning. At last, two special instances for economic census were performed, highlighting the performance of this approach.